Nuevas figuras jurídicas y lecturas interdisciplinarias: Debates jurídicos e interdisciplinarios frente a la incorporación de algunas figuras jurídicas y el rol de tecnología en procesos de apropiación cultural - Romero Medrano, Luis Fernando (Corporación Universitaria Americana, 2020)
Guarantorism and other philosophical-legal currents at the beginning of the century marked processes of legal innovation to the extent that they began processes of legal implementation, copying of models that worked in other legal systems and mergers, adaptations, articulations, among other possibilities of creation in the law. Two decades later, this type of legal creation and innovation has been exacerbated by the incorporation of technology in the law, in the way in which the law is interpreted, in the new problems that arise, and also in changes in the way of conceiving and relating to the world.